2004
DOI: 10.1525/si.2004.27.2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Portable Community: Mobility and Modernization in Bluegrass Festival Life

Abstract: Drawing from six years of ethnographic field research, I examine participants' involvement in bluegrass music and festival culture in the American West. Participants left their community-starved home neighborhoods to cultivate what I refer to as "portable communities": temporary forms of mobile gemeinschaft community that participants found in multiple settings. Festivalgoers articulated a consistent vocabulary of intimacy, inclusion, and simplicity when describing their continued involvement in this setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 35 publications
2
49
0
1
Order By: Relevance
“…This reasoning is consistent with prior research on events that has highlighted the importance of attendees identifying with the festival community as a possible explanation of attachment to an event, and of adopting the dominant behaviour accepted by the festival's community (Adsett, 2011;Bhattacharya, Rao, & Glynn, 1995;Gardner, 2004;Hays & Minichiello, 2005). For instance, Bhattacharya et al's (1995) study into art museum members' perceived belongingness to the organisation found three main elements that are related to the members' identification with the museum community: 1) organisational and product characteristics such as the perceived organisational prestige; 2) members' affiliation characteristics, for example, duration of membership, frequency of visits; and 3) members' activity characteristics such as donating activity and being able to confirm their expectations of the organisation's services.…”
Section: Festival Attachmentsupporting
confidence: 89%
See 1 more Smart Citation
“…This reasoning is consistent with prior research on events that has highlighted the importance of attendees identifying with the festival community as a possible explanation of attachment to an event, and of adopting the dominant behaviour accepted by the festival's community (Adsett, 2011;Bhattacharya, Rao, & Glynn, 1995;Gardner, 2004;Hays & Minichiello, 2005). For instance, Bhattacharya et al's (1995) study into art museum members' perceived belongingness to the organisation found three main elements that are related to the members' identification with the museum community: 1) organisational and product characteristics such as the perceived organisational prestige; 2) members' affiliation characteristics, for example, duration of membership, frequency of visits; and 3) members' activity characteristics such as donating activity and being able to confirm their expectations of the organisation's services.…”
Section: Festival Attachmentsupporting
confidence: 89%
“…Gardner's (2004) Although festival attachment was identified by managers and attendees as a factor influencing environmentally responsible behaviour at music festivals, it is important to note that the current research's quantitative analysis results show that place attachment is a better predictor than festival attachment of both environmentally responsible behavioural intentions and actual behaviours.…”
Section: Festival Attachmentmentioning
confidence: 64%
“…This is also what is usually implied by colloquial use of the term community by politicians and other stakeholders. While it can be argued that the concept of a community is widely understood and does not need to be defined (Creed, 2006), it has also been described as having a wide range and variety of meanings (Gardner, 2004). The difficulty lies in the values that are inherent in the word and the different ways in which it is used (Creed, 2006).…”
Section: Exploring the Communitymentioning
confidence: 99%
“…Hints at diversity were reported by Gardner (2004), for example, who claims that people from a wide variety of educational, occupational and religious backgrounds mingle at bluegrass festivals and Willems-Braun's (1994) study of Canada's fringe festivals warns that the attendees cannot be un-problematically categorised into social groups due to the possibilities of multiplicities within individuals and within the festival space. Curtis (2010) also suggests that new social connections are made between jazz festival performers, leading to new musical collaborations.…”
Section: Focus On Festivalsmentioning
confidence: 99%